2018
DOI: 10.1254/jpssuppl.wcp2018.0_po1-11-11
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and disposition kinetic of Cucurbitacin B in rats

Abstract: Background: Cucurbitacin B is an oxygen-rich containing triterpene which can be found mainly in Trichosanthes cucumerina. Cucurbitacin B gains some interests due to it exerts numerous pharmacological effects particularly antiinflammation and antitumor activity. Although Cucurbitacin B has been studied extensively in its pharmacological properties, the pharmacokinetic information in mammals of Cucurbitacin B is very limited. Thereby, this study aims to investigate the pharmacokinetic profiles of Cucurbitacin B … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…Cucurbitacin B is the most studied compound among all cucurbitacins, and hence, the literature information about the bioavailability and safety of this compound is the most comprehensive. Experiments with Wistar rats have shown that the oral bioavailability of cucurbitacin B was 10%, with the highest concentration in plasma ranging from 1 to 100 ng/mL and reaching maximum value approximately within 30 min [380]. Moreover, cucurbitacin B displayed a high tissue-to-plasma ratio, accumulating around 10-fold in several organs.…”
Section: The Bioavailability and Safety Of Compounds Reviewedmentioning
confidence: 99%
“…Cucurbitacin B is the most studied compound among all cucurbitacins, and hence, the literature information about the bioavailability and safety of this compound is the most comprehensive. Experiments with Wistar rats have shown that the oral bioavailability of cucurbitacin B was 10%, with the highest concentration in plasma ranging from 1 to 100 ng/mL and reaching maximum value approximately within 30 min [380]. Moreover, cucurbitacin B displayed a high tissue-to-plasma ratio, accumulating around 10-fold in several organs.…”
Section: The Bioavailability and Safety Of Compounds Reviewedmentioning
confidence: 99%